Governance and State-Owned Enterprises : How Costly is Corruption? - Baum, Anja.; Hackney, Clay.; Medas, Paulo; Sy, Mouhamadou (Washington, D.C. : International Monetary Fund, 2019)
State-owned enterprises (SOEs) are present in key sectors of the economies around the world. While they can provide an important public service, there is widespread concern that their activities are negatively affected by corruption. However, there is limited cross-country analysis on the costs of corruption for SOEs. We present new evidence on how corruption affects the performance of SOEs using firm level data across a large number of countries. One striking result is that SOEs perform as well as private firms in core sectors when corruption is low. Taking advantage of a novel database reforms, we also show that SOE governance reforms can generate significant performance gains.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet